Efeitos do exercício físico de intensidade moderada sobre parâmetros sistêmicos e cardíacos da sobrecarga crônica de ferro em ratos - Ávila, Renata Andrade (2021)
Background and goals: Iron is an essential micronutrient in several vital processes and maintenance of body homeostasis. However, its excess can cause organ damage, mainly due to the oxidative stress observed in this condition, with cardiomyopathy being the main cause of death in patients with iron overload. Although exercise has long been considered a cardioprotective tool, its effects on iron overload are unknown. This study was designed to investigate the effects of moderate-intensity aerobic training in a rodent model with chronic iron overload. Materials and methods: Wistar rats received intraperitoneal injections of iron-dextran 100 mg/kg/day, 5 days/week for 4 weeks and then were kept untrainedor submitted to physical exercise on a treadmill (60 min/day, progressive aerobic training at 60-70% of maximum speed, 5 days/week) in the following 8 weeks. At the end, left ventricular hemodynamics were assessed, and blood, liver and heart samples were collected. In addition, myocardial mechanics was studied “in vitro” in isolated left ventricular papillary muscles, and cardiac remodeling was evaluated by histology and immunoblotting. Main results: The protocol adopted in the study was efficient in developing the chronic iron overload model in which serum iron levels remained increased and transfer saturation also maintained above 20-50%, consistent with what is found in patients with these conditions. Confirming the experimental model, iron overload led to liver iron deposition and fibrosis and increased serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST). In addition, cardiac iron accumulation was accompanied by impaired myocardial mechanics, increased cardiac collagen type I and lipid peroxidation (TBARS), and serum CK-MB release. Although moderate-intensity exercise did not influence iron levels, injury markers (AST, CK-MB and TBARS) were significantly reduced in association with an increase in the endogenous antioxidant enzyme catalase. Likewise, myocardial contractility and inotropic responsiveness to calcium and isoproterenol were improved in exercised rats, as were the phosphorylation levels of phosphorylated substrates by PKAConclusion: Moderateintensity aerobic exercise attenuated cardiac damage and oxidative stress in this experimental model, and thereby may represent a potentially useful nonpharmacological adjuvant therapeutic tool for iron overload cardiomyopathy.